The Contribution of Hand Eye Coordination and Arm Muscle Strength to the Accuracy of Smash in Beach Volleyball Athletes PBVSI Bengkulu City - Dodi Ertanto; Dwingki Marta Putra; Megi Personi (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the Contribution of Hand Eye Coordination and Arm Muscle Strength to the Accuracy of Smash in Men's Beach Volleyball Athletes PBVSI Bengkulu City. This type of research is correlational or correlational research. The subjects of this research were 30 PBVSI Beach Volleyball Athletes in Bangkulu City. The instruments and data collection techniques used in this study were throwing and catching tennis balls, arm muscle strength tests, hanging and lifting tests, and smash accuracy tests in volleyball games. The results showed that there was a contribution between hand eye coordination and arm muscle strength on the accuracy of smash in male beach volleyball athletes PBVSI Bengkulu City, that arm muscle strength had a contribution rate of 92.16% for smash in volleyball, which means there are many other factors that contribute. on smash skills in volleyball games.